Prediction of the load and deflection response of concrete deep beams reinforced with FRP bars. Issue 1 (2nd January 2021) - Thomas, Job; Ramadass, S.
Abstract: The load and deflection response of six concrete deep beams longitudinally reinforced with glass fiber-reinforced polymer (GFRP) bars having shear span to depth ratio of 0.5 to 1.0 were presented in this paper. The existing model originally proposed for the prediction of shear strength and the deflection at the ultimate stage of concrete deep beams longitudinally reinforced with steel reinforcement, using the Softened Strut- and-Tie (SST) concept is modified to account for the influence of FRP longitudinal bars in the deep beam. The magnitude of strut efficiency factor was proposed based on the regression analysis of 47 test data. The model is useful for the prediction of load and deflection response of FRP reinforced concrete deep beams up to ultimate stage. The degradation of the stiffness due to the progressive cracking of the concrete is accounted for in this model. The predicted load-deflection response of the six test beams in this study was found to be comparable to the corresponding experimental data. The load and the mid-span deflection at ultimate stage of 53 simply supported deep beams longitudinally reinforced with FRP bars were also predicted using the proposed model. The mean of the ratio of the experimental load to the predicted load and deflection at ultimate stage for the 53 beams is found to be 1.05 and 1.03 respectively with the corresponding coefficient of variation (CoV) of 29.5% and 40.8% respectively.